Experimental study of person-centered psychotherapy in somatogenic disorders treatment (A study of chronic gastrointestinal diseases) - Bondarenko, Alexandr F.; Maksimenko, Ksenia S. (Psychological Counseling and Psychotherapy, 2019)
This article touches upon the problem of Person-centered psychotherapy in the treatment of specific psycho-emotional problems caused by chronic physical illnesses. The study involved the patients with chronic diseases of gastroenterological spectrum on the exacerbation stage. Total sample size was 144 people: 85 females (59.09%) and 59 males (40.01%) at the age from 24 to 59 y. The average duration of therapy ranged from 15 to 20 hours. A separate group of patients (15 people) were treated with medications prescribed by a psychiatrist in accordance with psychopathological report taking into account the basic diagnosis (anxiolytic, sedative, nootropic, anti-depressants).Methods. At the sample selection and the final stages the MMPI, M. Luscher Colour Test and L. Szondi Test were applied. Before and after each therapeutic session express-diagnostics via SAM- techniques (self-esteem, activity, mood), in form of personal semantic differential was applied.Results and conclusions. The most significant results in terms of clinical features (health, strengthening, stress reduction, reduction of scales’ peaks, indicating the severity of the reactive state, positive dynamics of the lab tests, etc.) have been observed in the group of patients receiving concomitant (psychological, pharmacological and nosology-oriented) therapy. It may be assumed that various psychotherapeutic approaches should be considered as subsidiary, rather than principal, means of chronic illness treatment. Psychological methods proper would be useful for emotional abreaction, switching attention from the dominant physical suffering to the patient's personal resources, as well as self-presentation processes.